Associations between body mass index and pubertal development based on the outcomes of girls with early breast development - Zhao, Manman; Liu, Meijuan; Cao, Bingyan; Gong, Chunxiu (Frontiers in Endocrinology, 2022)
Objective: To investigate the associations between physical and pubertal development based on the breast development outcomes in girls. Methods: This was a retrospective study. A total of 452 girls aged 6~8 years were included. Based on their breast development outcomes, the patients were divided into an idiopathic central precocious puberty (ICPP) group and a premature thelarche (PT) group. Anthropometry included measurements of height, weight, and BMI. ICPP was diagnosed when five diagnostic criteria from the current guidelines were met. Results: The girls with breast development at initial evaluation had a median age of 6.9 years. In total, 31.4% of patients were diagnosed with ICPP, and ICPP was rare in girls <7 years old (19%). Patients who presented with recurrence of breast development in the PT group accounted for 38.4%. At initial evaluation, the height, weight, BMI and bone age (BA) of the girls in the PT group corresponded to those of a normally developing girl at ages 7.8 years, 8.2 years, 8.6 years and 7.6 years, respectively. The girls in the ICPP group had a mean age of 7.3 years, and their mean height, weight, and BMI were 129.6 cm, 28.4 kg, and 17.0 kg/m2, which corresponded to the mean of a normally developing girl at ages 8.5 years, 9.1 years, and 10.5 years, respectively; these patients had BA of 9.2 years. Additionally, based on receiver operating characteristic (ROC) curve analysis, when the basal luteinizing hormone (LH) level was 0.32 IU/L and BMI reached 16.4 kg/m2, CPP was diagnosed in patients meeting all five diagnostic criteria for CPP, and the specificity and sensitivity were 71.9% and 88.2%, respectively. Conclusions: Girls with breast development before 8 years old had a high proportion of recurrence of breast development. The physical development of these girls at the time of breast development preceded that of normally developing girls by 1-2 years. BMI is an independent risk factor for early pubertal development, and is a simple and clear predictor of ICPP. In addition to the five classic diagnostic criteria, CPP is diagnosed when physical development corresponds to the mean for a 10.5 years old girl.